The effect of acuspike exercises in some biochemical variables and the transmitting accuracy facing from the top for the young players in volleyball - Dr. Saddah Ibraheem Saidwaly (الرياضة المعاصرة)
The use of training exercises in learning and training is now a major stone and important in this aspect, so the researcher wanted to use the acuspike device after determining the existence of some weakness in some of the variant of the skills of the transmitter of the face of the top (tennis) in volleyball, Direct and effective in achieving a point directly or back a weak ball from the opponent team to build a successful attack, the aim of the research to identify the impact of exercises in the acuspike in the development of some kinetic variables and their relation to the accuracy of the forward facing of the top of the players in the volleyball, A team of 12 players from the Diyala team .